Potential of Gracilaria Canaliculata Seaweed as Raw Material for Bioethanol Production from Menganti Beach Kebumen and Karang Bolong Beach Cilacap - Novella, Rizal Berlian; Widyartini, Dwi Sunu; Prabowo, Romanus Edy (Metamorfosa: Journal of Biological Sciences, 2022)
Seaweed is a source of foreign exchange and a source of income for coastal communities. Besides being used as food, drink, and medicine, seaweed which is rich in cellulose is very useful to become bioethanol. Bioethanol is used as a raw material for the manufacture of ethanol derivatives. The research objective was to sea the biomass and bioethanol content in Gracilaria canaliculata seaweed from Karang Bolong Beach, Cilacap, and Menganti Beach, Kebumen. Analysis of bioethanol data was carried out using the T-test with the SPSS program to determine whether there were differences in the bioethanol content of Gracilaria canaliculata from Menganti Beach, and Karang Bolong Beach, while the environmental monitoring test with biomass used the PRIMER 7 program for the most influential environmental factors. The results of the study showed there is evidence of environmental factors at Menganti Kebumen Beach and Gracilaria canaliculata biomass, the most influential of which are nitrate. The results of the test to maintain environmental factors of Menganti with Gracilaria canaliculata seaweed biomass using the BIOENV Primer 7 program analysis showed a fixed value on the nitrate display with a value of 0.852 while in the waters of Karang Bolong the value was recorded at 0.79. The T-test results showed no significant difference in the bioethanol content of Gracilaria canaliculata from Menganti Beach, Kebumen, and Karang Bolong Beach, Cilacap. Gracilaria canaliculata from Menganti Beach, Kebumen, produced an average bioethanol content of 7.07%, while those from Karang Bolong Beach Cilacap produced an average bioethanol content of 7.21%.